Êvgen Olesnic′kij : tri ìpostasì provìdnika – pravnik, polìtik, organìzator - Andrusâk, Taras (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
The activity and the formation of the outlook of Yevhen Olesnytskyy are examined in the article. Three spheres in which he acted are defined. 1. Legal activity of Yevhen Olesnytskyy, including his practical work as a lawyer; scientific and organizational legal work, in particular, creation of periodical «Legal Chasopys», fellowship in Shevchenko Scientific Society, an active part in its legal commission; spreading of legal knowledge publications in press, appearance on public meetings and in reading rooms. 2. Yevhen Olesnytskyy as a politician was the deputy of Diet of Galicia, the leader of Ukrainian faction in diet; the deputy of Viennese parliament; one of the founders and the leading figure of Ukrainian National Democratic Party. 3. Organizational activity of Yevhen Olesnytskyy can be conditionally divided into organization of economic structures and institutions and their management; organization of cultural institutions, publishing activity and theatre activities.
Keywords: Ołesnicki, Jewhen (1860-1917); prawnik; polityk; organizator